Odpowiedzi

2010-02-25T18:36:43+01:00
A)1/2x-3/4[x-(4x+1)]=1- x+1/4
1/2x - 3/4[x-4x-1]=5/4-x
1/2x - 3/4x + 3x + 3/4= 5/4 - x
-2x -x = -3/4 + 5/4
- 3x = 1/2/(-3)
x = - 1/6

b)2/3(3x-1)-3/2[2x+3(x-2)]=1
2x - 2/3 - 3/2 [2x +3x-6] = 1
2x - 2/3 - 3x -9/2x + 9 = 1
2x -3x - 9/2x = 2/3 -9 +1
- 11/2x = -22/3 / (-11/2)
x = 22/3 = 7 1/3
Najlepsza Odpowiedź!
  • kotq
  • Rozwiązujący
2010-02-25T18:37:04+01:00
1/2x - 3/4[4x-x]=1-x+1/4
(1/2x-3x-x=1-x+1/4)*4
4*1/2x-3x*4-x*4=4-4x+4*1/4
2x-12x-4x=4-4x+1
2x-12x-4x+4x=4+1
-10x=5//-10
x=-2

nie jestem pewna czy nie pomyliłam gdzieś znaków i czy nie będzie 2 ;)

2x-2/3-3/2[2x+3x-6]=1
2x-2/3-3x-9/2x+9=1
(2x-3x-9/2x1-9+2/3)*6
6*2x-3x*6-9/2x*6=6-6*9+2/3*6
12x-18x-27x=6-54+6
-33x=-42//-33
x=1,27